Converting Biomass and Waste Plastic to Solid Fuel Briquettes - Zannikos, F.; Kalligeros, S.; Anastopoulos, G.; Lois, E. (Journal of Renewable Energy, 2013)
This work examines the production of briquettes for household use from biomass in combination with plastic materials from different sources. Additionally, the combustion characteristics of the briquettes in a common open fireplace were studied. It is clear that the geometry of the briquettes has no influence on the smoke emissions. When the briquettes have a small amount of polyethylene terephthalate (PET), the behavior in the combustion is steadier because of the increase of oxygen supply. The smoke levels are between the 3rd and 4th grades of the smoke number scale. Measuring the carbon monoxide emission, it was observed that the burning of the plastic in the mixture with biomass increases the carbon monoxide emissions from 10% to 30% as compared to carbon monoxide emission from sawdust biomass emissions which was used as a reference.